Yemeni women’s role in conflict resolution - Domingues, Elisabete Júlio (2022)
This article looks at the topic of the role of Yemeni women in conflict resolution in Yemen, regarding the informal and formal peace processes. This study analyses scientific literature and documentation available in open sources, such as newspaper articles and interviews, along with non-governmental organizations' reports. It was also conducted some interviews with experts from different backgrounds connected to Yemen, which gives us a broader perspective of Yemeni women and their role in the conflict. It was found that women's participation in conflict resolution is an important piece that contributes to sustainable peace. Despite that, women have deep difficulties when we talk about assuming an active role in these stages and have been excluded from the negotiations in conflict resolution processes. Guided by the Security Council Resolution 1325, women's involvement in peace negotiations is one of the United Nations (UN) purposes. Even if the conflict parties in Yemen have been extremely resistant to accept them in negotiations, the UN has promoted their inclusion in formal processes, through some indirect adviser mechanisms, such as the Yemeni Women’s Pact for Peace and Security, the Yemeni Women’s Technical Advisory Group, and more recently, the Bloc of Women Members of Political Parties. The patriarchal Yemeni society has limited the Yemeni women intervention in the conflict, still, they have taken part in it, by participating in many activities, like evacuating civilians and taking care of injured in areas affected by war, negotiating humanitarian access, and exchange of prisoners, which shows the dynamic and relevant position they have in conflict resolution informal processes.